Chitosan shaping and sample preparation method for high-salt sample TXRF analysis
Through the preparation method of mixing chitosan acetic acid solution and high-salt solution and heating and drying, the problem of salt supersaturation and precipitation of high-salt samples in TXRF analysis is solved, the sample surface flatness and detection accuracy are achieved, and the analysis efficiency and safety are improved. sex.
Patent Information
- Application Number
- CN202411367218.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
During the TXRF analysis, high-salt content samples have particle size effects due to salt oversaturation and precipitation, which affects the accuracy of the analysis results. Conventional drying and sample preparation methods will damage the instrument probe and cause matrix effects, affecting detection efficiency and accuracy.
The chitosan acetic acid solution is mixed with the high-salt solution, and then dried by dropping it to the surface of the carrier and heating it to prepare a sample with a flat surface to avoid salt crystallization and solid-liquid mixed phases, and improve the uniformity of the sample and detection accuracy.
This method improves the efficiency and practicality of TXRF analysis of high-salt samples, ensures flat surface of the sample, reduces instrument damage, enhances the reliability of analysis results, and does not require the use of toxic and harmful reagents, which are simple to operate, low-cost, and are manufactured. The sample process is fast.
Smart Images

Figure CN119224025A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material element detection and analysis, and particularly relates to a chitosan shaping sample preparation method for TXRF analysis of high-salt samples. Background Art
[0002] Total reflection X-ray fluorescence (TXRF) analysis technology is a multi-element analysis technology suitable for measuring trace elements in trace samples. It uses primary X-rays or other charged particles to excite atoms in the substance to be tested, generating secondary characteristic X-ray fluorescence to analyze the material composition and chemical form. It is widely used in environmental science, geology, biomedicine and other fields because of its small sample volume (μL or ng), short analysis time (100-1000 seconds), simple quantification, low element detection limit, good economy and simultaneous detection of multiple elements.
[0003] During TXRF analysis, conventional liquid or suspension samples can be directly dried and prepared through simple treatment. However, for samples with high salt content, the salt content is at least 0.1% and the saturation is high. When heated and dried, crystals will be precipitated due to water loss. Special salt crystals will also hinder drying, presenting a coexistence state of surface crystals and internal solid-liquid mixed phases, increasing the overall thickness of the matrix, causing damage to the instrument's probe and affecting the normal operation of the instrument. At the same time, thicker sample spots are accompanied by serious matrix effects, which limits the accuracy of the element analysis results.
[0004] In the TXRF analysis process, a suitable sample preparation method is a prerequisite for accurate measurement. Direct sampling and drying of samples with high salt content will face the particle size effect caused by salt supersaturation precipitation, which will affect the accuracy of the analysis results. Therefore, it is particularly important to choose a suitable sample preparation method for TXRF analysis of high-salt matrices.
[0005] Therefore, a rapid sample preparation method for TXRF detection of high-salt samples is urgently needed to improve the efficiency and practicality of TXRF analysis of high-salt samples. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a chitosan shaping sample preparation method for high-salt sample TXRF analysis. The sample prepared by the method has a smooth and uniform measurement surface, and the method improves the efficiency and practicability of TXRF detection of high-salt samples.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A chitosan shaping sample preparation method for high-salt sample TXRF analysis comprises the following steps: step 1, preparing a chitosan acetic acid solution; step 2, mixing a high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution; step 3, dropping the mixed solution onto a carrier surface, heating and drying, to obtain a high-salt test sample for TXRF detection.
[0009] Furthermore, in the step 1, the preparation method of the chitosan acetic acid solution is: mixing chitosan powder with acetic acid solution, stirring and mixing to obtain a chitosan acetic acid solution, and standing for 1 hour to defoam; in the chitosan acetic acid solution, the weight percentage concentration of chitosan is 1-4%, and the weight percentage concentration of acetic acid is 2%; the chitosan powder is chitosan powder with a deacetylation degree of ≥95%.
[0010] Furthermore, the stirring method is stirring by a magnetic stirrer, and the stirring time is 30 minutes to 40 minutes.
[0011] Furthermore, in step 2, the salt in the high-salt solution sample is an inorganic salt; in the high-salt solution sample, the weight percentage concentration of the inorganic salt is not less than 0.1%, and the mass volume concentration of the element to be measured is not less than 5 mg / L.
[0012] Furthermore, the inorganic salt is one or more of sodium chloride, potassium chloride, magnesium chloride and calcium chloride.
[0013] Furthermore, in the step 2, in the mixed solution, the weight percentage concentration of salt is 0.5-2%, and the weight percentage concentration of chitosan is 0.1-0.8%.
[0014] Furthermore, in step 2, the high-salt solution sample is a sample in which the sample itself is an aqueous solution or an aqueous solution sample made from a solid sample.
[0015] Furthermore, in the step three, the mixed solution is added dropwise to the center of the carrier surface using a pipette, and the sampling volume of the pipette is 5 to 10 μL; and the carrier is quartz glass.
[0016] Furthermore, in step three, the heating temperature is 50° C. and the drying time is 3 min to 5 min.
[0017] Beneficial effects:
[0018] (1) The present invention provides a chitosan shaping sample preparation method for TXRF analysis of high-salt samples. The method is applied to the preparation of high-salt samples. For solutions with high salt content, the surface of the prepared sample is uniform and flat, which meets the actual measurement requirements. The damage to the instrument probe caused by the increase in matrix thickness caused by surface crystallization and the coexistence of internal solid-liquid mixed phases is avoided, and the matrix effect caused by the sample spot thickness is reduced, thereby improving the reliability of the analysis results.
[0019] (2) Compared with the adsorption method and the direct dilution method, the present invention does not require the addition of toxic and harmful reagents to enrich the elements to be tested or to digest the matrix, which is safe and environmentally friendly;
[0020] (3) The sample preparation process of the present invention is simple to operate, low in cost, greatly shortens the sample pretreatment time, and the measurement results of the prepared samples have good uniformity and repeatability, which can meet the needs of actual detection. Among them, the heating step in the sample preparation process is to completely dry the sample on the one hand, and to control the temperature so that the chitosan is completely film-formed while reducing the thickness of the coffee ring, thereby improving the detection accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic flow chart of the chitosan shaping sample preparation method for TXRF analysis of high-salt samples of the present invention;
[0022] Figure 2 The following are appearance pictures of the sample prepared in Example 1 of the present invention before shaping (left) and after shaping (right);
[0023] Figure 3 This is the TXRF detection spectrum of the standard sample prepared before chitosan shaping;
[0024] Figure 4 is the TXRF detection spectrum of the standard sample prepared in Example 1 of the present invention;
[0025] Figure 5 is the TXRF detection spectrum of the salt lake brine sample prepared in Example 2 of the present invention;
[0026] The accompanying drawings are marked as:
[0027] 1. Solution to be tested; 2. Pipette; 3. Heating plate. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.
[0030] Example 1
[0031] This embodiment provides a chitosan shaping sample preparation method for TXRF analysis of high-salt samples, comprising the following steps:
[0032] Step 1: Prepare chitosan acetic acid solution:
[0033] The chitosan powder was mixed with the acetic acid solution, stirred by a magnetic stirrer for 40 minutes, and allowed to stand for 1 hour to defoam, to obtain a chitosan acetic acid solution;
[0034] The chitosan powder is chitosan powder with a deacetylation degree of ≥95%. In the chitosan acetic acid solution, the weight percentage concentration of chitosan is 2%, and the weight percentage concentration of acetic acid is 2%.
[0035] Step 2: Mix the high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution:
[0036] (1) Prepare a high-salt solution sample to be tested: mix solid sodium chloride, potassium chloride, magnesium chloride and calcium chloride with water, and add standard solutions of rubidium and cesium as the elements to be tested to obtain a high-salt solution standard sample to be tested.
[0037] (2) Preparing a mixed solution: Mixing the high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution. In the mixed solution, the weight percentage concentration of the inorganic salt is 2%, the weight percentage concentration of the chitosan is 0.5%, and the mass volume concentration of the rubidium and cesium elements is 20 mg / L.
[0038] Step 3: Prepare test samples:
[0039] Heat the heating plate to 50°C, use a pipette to draw 10 μL of the mixed solution in step 2 and drop it onto the center of the quartz glass surface, and place it on the heating plate to dry for 5 minutes. The sample preparation is completed to obtain a high-salt test sample for TXRF detection.
[0040] The sample preparation method without adding chitosan acetic acid solution was used as a comparative example. The appearance of the test samples prepared in the comparative example and the present embodiment is shown in FIG. Figure 2 The samples of this embodiment and the comparative example were subjected to TXRF analysis under the following measurement conditions: 20 kV, 400 μA, 300 s. Figures 3-4 As shown. Figures 3-4 It can be seen that the addition of chitosan improves the sample morphology, achieves the purpose of shaping, and increases the net count of elements. The peaks of the Rb and Cs elements to be measured are significantly enhanced. The increase in net counts also reduces the detection limit and improves the accuracy of the measurement.
[0041] Step 4: Reliability evaluation:
[0042] 1. According to the preparation method of this embodiment, 3 samples were prepared repeatedly, and 5 positions of the 3 test samples were measured, and the characteristic peak counts of rubidium and cesium elements were recorded to evaluate the uniformity of the test samples and the reliability of the sample preparation method. The results are shown in Table 1. As can be seen from Table 1, the elements in the samples prepared by the sample preparation method are evenly distributed, and the relative standard deviation of the fluorescence intensity measurement values of rubidium and cesium elements at different positions of each sample does not exceed 3.91%, indicating that the prepared samples have good uniformity.
[0043] Table 1: Relative standard deviation of Rb and Cs elements measured at different positions of three samples
[0044]
[0045] 2. According to the preparation method of this embodiment, 3 samples were prepared repeatedly, and the same position of the 3 samples was tested (each sample was tested 4 times), and the characteristic peak counts of the rubidium and cesium elements were recorded to evaluate the repeatability of the sample preparation method, and then to evaluate the reliability of the sample preparation method. The results are shown in Table 2. As can be seen from Table 2, after 3 repeated samplings, the relative standard deviations of the net counts of rubidium and cesium were 3.55% and 3.14%, respectively. The sample preparation repeatability is good, indicating that this method can be stably and reliably applied to the measurement of elements in high salt content solutions.
[0046] Table 2: Relative standard deviation of Rb and Cs elements measured at the same position of 3 samples
[0047]
[0048]
[0049] Example 2
[0050] This embodiment provides a chitosan shaping sample preparation method for high-salt sample TXRF analysis to prepare a test sample of salt lake brine for TXRF detection, comprising the following steps:
[0051] Step 1: Prepare chitosan acetic acid solution:
[0052] The chitosan powder was mixed with the acetic acid solution, stirred by a magnetic stirrer for 40 min to obtain a chitosan acetic acid solution, and allowed to stand for 1 h to defoam;
[0053] The chitosan powder is chitosan powder with a deacetylation degree of ≥95%. In the chitosan acetic acid solution, the weight percentage concentration of chitosan is 2%, and the weight percentage concentration of acetic acid is 2%.
[0054] Step 2: Mix the high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution:
[0055] The chitosan acetic acid solution obtained in step 1 was mixed with the salt lake brine sample and water in a ratio of 1:1:6 to obtain a mixed solution. At this time, the total solid solubility in the solution was 5.07 g / L.
[0056] Step 3: Prepare test samples:
[0057] Heat the heating plate to 50°C, use a pipette to draw 8 μL of the mixed solution in step 2 and drop it onto the center of the quartz glass surface, and place it on the heating plate to dry for 5 minutes. The sample preparation is completed to obtain a high-salt test sample for TXRF detection.
[0058] Step 4: Effect verification
[0059] The samples prepared in this example were subjected to TXRF analysis, with rubidium and cesium as the detection objects, and the measurement conditions were: 20 kV, 400 μA, 300 s. The results are shown in Figure 2. Figure 5 shown.
[0060] The rubidium and cesium in the salt lake brine samples were detected by ICP-MS method. The test results are shown in Table 3.
[0061] As shown in Table 3, compared with the ICP-MS results, the maximum error of this embodiment is less than 15%. It can be seen that the sample preparation method provided by this application can achieve shaping and rapid sample preparation, and the accuracy can meet the measurement requirements.
[0062] Table 3
[0063] Element concentration (mg / L) ICP-MS TXRF R 22.46 25.10 Cs 9.69 10.53
[0064] Example 3
[0065] This embodiment provides a chitosan shaping sample preparation method for high-salt sample TXRF analysis to prepare a saline wastewater test sample for TXRF detection, comprising the following steps:
[0066] Step 1: Prepare chitosan acetic acid solution:
[0067] Mix the chitosan powder with the acetic acid solution, stir with a magnetic stirrer for 30 to 40 minutes to obtain a chitosan acetic acid solution, and let it stand for 1 hour to defoam;
[0068] The chitosan powder is chitosan powder with a deacetylation degree of ≥95%. In the chitosan acetic acid solution, the weight percentage concentration of chitosan is 2%, and the weight percentage concentration of acetic acid is 2%.
[0069] Step 2: Mix the high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution:
[0070] The chitosan acetic acid solution obtained in step 1 was mixed with saline wastewater in a ratio of 1:3 to obtain a mixed solution. At this time, the total solid solubility in the solution was 7.5 g / L.
[0071] Step 3: Prepare test samples:
[0072] Heat the heating plate to 50°C, use a pipette to draw 8 μL of the mixed solution in step 2 and drop it onto the center of the quartz glass surface, and place it on the heating plate to dry for 5 minutes. The sample preparation is completed to obtain a high-salt test sample for TXRF detection.
[0073] Example 4
[0074] This embodiment provides a chitosan shaping sample preparation method for high-salt sample TXRF analysis to prepare a seawater test sample for TXRF detection, comprising the following steps:
[0075] Step 1: Prepare chitosan acetic acid solution:
[0076] Mix the chitosan powder with the acetic acid solution, stir with a magnetic stirrer for 30 to 40 minutes to obtain a chitosan acetic acid solution, and let it stand for 1 hour to defoam;
[0077] The chitosan powder is chitosan powder with a deacetylation degree of ≥95%. In the chitosan acetic acid solution, the weight percentage concentration of chitosan is 2%, and the weight percentage concentration of acetic acid is 2%.
[0078] Step 2: Mix the high-salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution:
[0079] The chitosan acetic acid solution obtained in step 1 was mixed with the seawater sample in a ratio of 1:7 to obtain a mixed solution. At this time, the total solid solubility in the solution was 5.22 g / L.
[0080] Step 3: Prepare test samples:
[0081] Heat the heating plate to 50°C, use a pipette to draw 8 μL of the mixed solution in step 2 and drop it onto the center of the quartz glass surface, and place it on the heating plate to dry for 5 minutes. The sample preparation is completed to obtain a high-salt test sample for TXRF detection.
[0082] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0083] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A chitosan shaping sample preparation method for high-salt sample TXRF analysis, characterized in that: The following steps are involved: Step 1, preparing chitosan acetic acid solution; Step 2, mixing the high salt solution sample to be tested with the chitosan acetic acid solution to obtain a mixed solution; Step 3: Take the mixed solution and drop it onto the surface of the carrier, heat and dry it to obtain a high-salt test sample for TXRF detection.
2. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 1, the chitosan acetic acid solution is prepared by: Mixing chitosan powder with acetic acid solution, stirring and mixing, to obtain chitosan acetic acid solution; In the chitosan acetic acid solution, the weight percentage concentration of chitosan is 1-4%, and the weight percentage concentration of acetic acid is 2%.
3. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 2, characterized in that: The stirring method is stirring by a magnetic stirrer, and the stirring time is 30 minutes to 40 minutes.
4. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 2, the salt in the high salt solution sample is an inorganic salt; In the high-salt solution sample, the weight percentage concentration of inorganic salts is not less than 0.1%, and the mass volume concentration of the element to be measured is not less than 5 mg / L.
5. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: The inorganic salt is one or more of sodium chloride, potassium chloride, magnesium chloride and calcium chloride.
6. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 2, in the mixed solution, the weight percentage concentration of salt is 0.5-2%, and the weight percentage concentration of chitosan is 0.1-0.8%.
7. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 2, the high-salt solution sample is a sample that is an aqueous solution or an aqueous solution sample made from a solid sample.
8. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 3, the mixed solution is added dropwise onto the surface of the carrier using a pipette, and the sampling volume of the pipette is 5 to 10 μL; The carrier is made of quartz glass.
9. The chitosan shaping sample preparation method for high-salt sample TXRF analysis according to claim 1, characterized in that: In the step 3, the heating temperature is 50° C. and the drying time is 3 min to 5 min.
